Hand motion and the generation of propulsive force of crawl swimmers - Matsuuchi, K.; Yamada, K.; Miwa, T.; Sakakibara, J.; Nomura, T. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
It is of great interest to researchers to understand in detail the propulsive forces induced during swimming. To understand better how these forces are generated it is necessary to know the flow field around a swimmer. However, it is difficult to obtain precise information about the flow field because there are no convenient tools to probe the complex and unsteady field. Recently, a sophisticated technique called PIV (Particle Image Velocimetry) has been employed in the analysis of the motion of front crawl swimmers [1]. From the measurements of the flow field obtained using PIV (where the geometrical parameter of the palm is obtained from motion analysis), it was concluded that the propulsive forces are directly related to the generated vortices. However, since only swimmers with an S-shaped palm trace were considered, more information about the unsteady flow dynamics is needed. In this study the investigation of the propulsive forces was extended to swimmers that have a wider stroke technique in the crawl swimming. Three different swimmers were used in the investigation: first, an elite crawl swimmer; second, a butterfly swimmer with a race career; and finally, for comparison, a beginner. The palm trace of the second swimmer is an S-shaped swimmer in his crawl swimming. Motion analysis was performed using two synchronized high-speed cameras to obtain geometrical information about the hand motion of the swimmers. The DLT method, which is standard in the biomechanics, was used to determine the positions in 3-dimensional real space from the 2-dimensional recorded information. Experiments were performed in a running water tunnel at the University of Tsukuba. After processing the data through a digital filter with a 40 Hz cut-off, motion analysis obtained the sequential positions of several fixed points of the swimmer`s palm. Angles of the swimmer`s palm relative to the water, the pitch and yaw angles, and the speed of the palm movement were determined from the analysis. PIV was employed to clarify the unsteady flow field arising from the hand movement. As a result, it was found that the hand speed of the beginner is somewhat larger than that of the other two swimmers. Furthermore, a significant change in the palm angle of the first two swimmers is observed during their stroke, whereas the change in the palm angle of the beginner is found to be considerably less. The PIV measurements reveal a significant amount of information about the vortices generated during the swimming stroke. The component of the momentum generation in the swimming direction of the two top swimmers is found to be greater than the momentum generated by the beginner. It was confirmed that the hand thrust force is directly related to the generation of vortices.